A bibliography of Australian whaling in the nineteenth century. (May 2015) - Howard, Mark
The bibliography deals with Australian pelagic and bay whaling in the nineteenth century. It starts with some general works on the subject, followed by entries on whaling in each of the states. It ends with a section on Australian whalers in New Zealand and another on scrimshaw. Most entries relate to books, chapters in books, and journal articles. Also listed are some unpublished items – including university theses and archaeological reports – as well as a few newspaper articles and websites. Some important reference works, such as published lists of ship arrivals and departures for the two main whaling ports of Sydney and Hobart, are also included. The bibliography was inspired by, and draws on, two earlier works about whaling in the Pacific by Honore Forster, The South Sea Whaler (1985) and More South Sea Whaling (1991). I would like to thank Martin Gibbs for providing a copy of the bibliography from his 1996 thesis on whaling in Western Australia.